ANALISIS PENAMPILAN KERJA ALAT PENYERAT PISANG ABACA (Musa textilis Nee1) - Chevin A.T Unsong; Dedie Tooy; Daniel P. M. Ludong (Universitas Sam Ratulangi, 2022)
ABSTRACT The purpose of this study was to analyze the work of the abaca banana fiber which consists of the fiber capacity, the fiber efficiency and the time required for the fiber. This research was conducted to provide specific information to abaca banana farmers and the community about the work process and the use of abaca banana fiber so that in the future they can develop existing tools. Abaca fiber is very useful for future product development because of the superiority of its fiber. To develop abaca fiber, one of them must be supported by the development of fiber equipment that is capable of fiber with high capacity and good fiber yield. This fiber tool uses diesel motor power as the engine driving YANMAR TF105 working power 9.5 DK/2400 rpm maximum 10.5DK/2400rpm, The working process of this abaca banana fiber is initially the banana stem midrib is cut and split according to the size of the abaca banana stem , the average length of banana stems in Essang is 2.5 m to 3 m. then the frond that had been split was inserted between the retaining plate and the cylinder of the fiber knife, here the fibering process took place, the frond that had become fiber was then hung in the drying area. In one hour the fiber is capable of absorbing 18 kg/hour so that in one day it can absorb 144 kg, the yield is 5.2380% so that in one day the abaca banana fiber can produce 27.49 kg of dry fiber.